A simplified He's frequency–amplitude formulation for nonlinear oscillators. Issue 1 (March 2022) - Ren, Zi-Yin
Derived from an ancient Chinese algorithm, He's frequency–amplitude formulation is an effective approach to finding an approximate solution of a nonlinear oscillator. In this article, based on He's formulation, a simplified formulation is proposed. Some nonlinear oscillators are adopted as examples to demonstrate the solving process using this simplified formulation. Through the demonstration, it can be seen that the solving process is simplified.